Targeting Inflammation in Primary Cardiovascular Prevention - Carbone, Federico; Liberale, Luca; Bonaventura, Aldo; Cea, Michele; Montecucco, Fabrizio (Current Pharmaceutical Design, 2016)
Background: In the last decade, the development of anti-inflammatory strategies emerged as new trend in cardiovascular (CV) pharmacotherapy. Anti-inflammatory properties have been previously identified in different classes of drugs used in primary CV prevention. However, the extent to which the modification of inflammatory profile contributes in determining CV outcome remains controversial. Methods: Focusing on potential beneficial effects in primary prevention, this narrative review provides a comprehensive and critical analysis of randomized clinical trials testing anti-inflammatory treatments in CV disease. Results: As upstream regulator of the hepatic production of C-reactive protein, tumor necrosis factor-α, interleukin (IL)-6 and IL-1 pathways early emerged as potential targets for CV prevention. More recently, additional strategies targeting lipoprotein-associated phospholipase A2, pro-protein convertase subtilisin/kexin type 9, and intracellular pathways (such as p38 MAPK and different isoforms of NADPH oxidase) have been tested. Conclusion: Conflicting results emerged from clinical trials, emphasized the need to characterize the inflammatory profile of the patients, to minimize the heterogeneity of study populations and to clarify the true value of CRP as specific biomarker of atherosclerosis-related inflammation.
Keywords: C-reactive protein